Pharmacological significance of nitrogen-containing five and six-membered heterocyclic scaffolds as potent cholinesterase inhibitors for drug discovery. (September 2022) - Obaid, Rami J.; Mughal, Ehsan Ullah; Naeem, Nafeesa; Al-Rooqi, Munirah M.; Sadiq, Amina; Jassas, Rabab S.; Moussa, Ziad; Ahmed, Saleh A.
Abstract: N -heterocycles are crucial due to their biological, chemical, and practical significance. They are heavily investigated in biological processes involving anticancer, anti-inflammatory, antibacterial, antiviral, anti-tumor, and antidiabetic studies. Therefore, in the present perspective, this review reports the most recent literature (2020–2021) aiming at five- or six-membered N -heterocyclic compounds that show inhibition against cholinesterase enzyme. Inhibition of the cholinesterase enzyme is a popular strategy for the management of numerous mental diseases. Cholinesterase inhibitors enhance cholinergic transmission directly by inhibiting the enzyme acetylcholinesterase (AChE) which hydrolyses acetylcholine. Furthermore, it has also been demonstrated that both acetylcholinesterase and butyrylcholinesterase play an important role in Aβ-aggregation during the early stages of senile plaque formation. Therefore, AChE and BChE inhibition have been documented as critical targets for the effective management of AD by an increase in the availability of acetylcholine in the brain regions and a decrease in the Aβ deposition.This review highlights various five and six-membered N- heterocyclic classes of cholinesterase inhibitors designed for the treatment of Alzheimer's disease (AD). Nitrogen heterocycles represent stimulating lead that could assist the improvement of therapeutics. This review aims to cover chemical and biological studies from the past two years that have described the search for novel N- heterocycles with promising cholinesterase inhibitory properties. Graphical Abstract: ga1 Highlights: Cholinesterases are fundamental players in the peripheral- & central nervous system. Different classes of N -based heterocycles can have potential anti-ChE activity. The review supports that synthetic N -based heterocycles can be promising anti-ChE agents.